Insulin Receptor Antibodies Inhibit Insulin Uptake by the Liver: In Vivo 123I-Insulin Scintigraphic Scanning and In Vitro Characterization in Autoimmune Hypoglycemia. (1st January 2001) - Dozio, N.; Sarugeri, E.; Scavini, M.; Beretta, A.; Belloni, C.; Dosio, F.; Savi, A.; Fazio, F.; Sodoyez-Goffaux, F.; Pozza, G.
Abstract: Background: Insulin receptor antibodies can induce severe hypoglycemia or insulin resistance in rare autoimmune syndromes. In vitro properties of these antibodies occasionally explain the clinical features of the syndrome, but direct evidence of their in vivo activity is poor. We studied a 58-year-old male with rheumatoid arthritis who presented with hypoglycemic coma. Methods and Results: Antibodies were detected by inhibition of 125 I-insulin binding to human insulin receptor-3T3 cells by the patient's serum. By immunofluorescence, they were immunoglobulin G of all four subclasses, immunoprecipitated insulin receptors from biotin-labeled cells, and triggered phosphorylation of the beta subunit of the insulin receptor. Insulin binding on the patient's red blood cells was markedly reduced. A biodistribution study after intravenous 123 I-Tyr A14 insulin showed a marked inhibition of tracer uptake by the liver, reaching 10% of the injected dose (controls, mean±SD, 21.1±1.7%; n=10). Time activity curves generated on the liver and on the heart were parallel, with a T1/2 of 11.5 minutes for both, suggesting that no specific uptake occurred in the liver, where tracer activity represented only the blood pool. Clearance of insulin from the blood was indeed slower than in controls and mainly occurred through the kidneys. Analysis of plasma 123 I-insulin immunoreactivity and trichloroacetic acid precipitate showed that insulin degradation did not occur as in normal controls. Conclusions: In this patient with hypoglycemic syndrome, insulin receptor antibodies with in vitro insulin-like activity are capable of blocking in vivo the access of insulin to the liver receptor compartment, as directly demonstrated by the markedly altered biodistribution of intravenously injected 123 I-insulin.